2013
DOI: 10.1007/s11250-013-0462-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings related to intramammary infections in meat-producing ewes

Abstract: The aim of this study was to investigate the relationship between clinical findings and bacterial isolation in milk samples of meat-producing ewes. The study was conducted in 17 commercial flocks and 550 udder halves from suckling Santa Ines ewes. Initially, the clinical examination of the mammary glands and teats was performed by visual inspection and palpation of the teats and udder halves; then a scoring system was devised for all the findings. After that, the strip cup test and the California mastitis test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…Subclinical and chronic mastitis may be difficult to detect, although physical indicators such as abnormalities in skin color, shape, consistency, hardness, and presence of lesions on the udders are indicative of the condition. Teat injuries and consistency of the udder as determined by palpation have been shown to be related to the incidence of mastitis confirmed by bacteriological tests ( 79 ).…”
Section: Resultsmentioning
confidence: 99%
“…Subclinical and chronic mastitis may be difficult to detect, although physical indicators such as abnormalities in skin color, shape, consistency, hardness, and presence of lesions on the udders are indicative of the condition. Teat injuries and consistency of the udder as determined by palpation have been shown to be related to the incidence of mastitis confirmed by bacteriological tests ( 79 ).…”
Section: Resultsmentioning
confidence: 99%
“…The palpation of the mammary gland was classified according to its consistency in normal (score 0), normal consistency with nodules (score 1) and firm consistency (score 2). Teats and mammary gland were classified by palpation in normal (score 0), thelitis (score 1) and cisternitis (score 2) (BLAGITZ et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that the same host may present different frames in each ceiling. The authors reported a case of S. aureus mastitis in a nulliparous goat with two infected ceilings, with the left roof evolving to acute catarrhal mastitis and the right to mastitis with gangrenous detachment [32,33].…”
Section: Etiologymentioning
confidence: 99%
“…The entry most often is via the galactogenic route and can occur systemically via the hematogenous route. All animals are susceptible, increasing the predisposition mainly according to age and number of lactations [14,24,28,33]. Subclinical mastitis predominates in the herds of small ruminants, presenting prevalence between 5% and 30%.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation